Pengaruh Gaya Hidup, Service Quality, dan Word Of Mouth terhadap Keputusan Pembelian Konsumen dalam Memilih Cafe Sebagai Tempat Hangout di CKC Corner Perisai Rantauprapat - Astri Bella Lestari; Siti Lam’ah Nasution; Junita Lubis (Fakultas Ekonomi Universitas 45 Surabaya, 2022)
This research aims to determine the influence of lifestyle, service quality, and word of mouth on consumer purchasing decisions in choosing a café as a hangout place at CKC Corner Shield Rantauprapat. This type of research is quantitative. In this study, the population is consumers of the CKC Corner Shield Rantauprapat café, the number of which is not known for certain. Because the population is unknown, the sample size obtained from the formula (Sujarweni, 2015) was 96 people. The sampling technique used is accidental sampling, that is, the sampling technique can be carried out on anyone who is accidentally found and is suitable to be used as a sample, then that person can be used as a sample. The research results show that lifestyle, service quality, and word of mouth have a positive and significant influence on consumer purchasing decisions in choosing a café as a hangout place at CKC Corner Shield Rantauprapat. The R square value from the coefficient of determination analysis is 0.606, meaning that purchasing decisions can be explained by lifestyle variables (x1), service quality (x2), and word of mouth (x3) of 60.6%, while the remaining 39.4% can be explained by other variables not examined in this study.